A STUDY ASSESSING THE IMPACTS OF NEW REGULATORY PROPOSALS ON CYCLICALITY OF CAPITAL REQUIREMENTS THE CASE OF THE CZECH REPUBLIC - Bartůsek, Michal; Chytil, Zdeněk, 1949-; Tříska, Dušan, 1946-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2012)
This work focuses on new regulatory proposals, primarily Basel III accords and analyzes its ability to create a buffer for recurrent credit bubbles. This paper follows a research made by Lis, Pagés and Saurina [2000]. Their paper has illustrated the cyclicality of loan growth and GDP growth for Spain. This cyclicality is supported by cyclical Basel II regulation. In this paper is examined the ability of new regulatory proposals such as Basel III, statistical provisions and change in the approach to the probability of default, to cope with recurrent credit bubbles. According to my critical assessment, Basel III may not be able to create sufficient capital buffer for exceptional credit bubbles such as the current one. This buffer suggested by Basel III has several drawbacks which may decrease its functionality. Statistical provision is not an appropriate measure either, because it could weaken the fair and true view of financial statements principle. Change in approach to probability of default seems to be rational and effective. The only issue may relate to its recovery mechanisms. It doesn't support economic growth in time of economic recession. The author's proposal of new countercyclical buffer, which would be based on credit-to-GDP ratio and GDP growth to loan growth gap is introduced at the end of this work. Although this measure may have negative impact on GDP growth, it may create an appropriate buffer to systematic credit risk.
Vedoucí práce: Zdeněk Chytil
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses